Digital Marketing Training through the 4C Formula Copywriting Method in Kampung Gerabah Penanggungan - Chaerani, Aura; Rahmawati, Widiya; Syaadzan, Daiva Permana Ardanu; Salamah, Salafiatus; Iswari, Hanif Rani (TGO Journal of Community Development, 2023)
This community service initiative focused on enhancing the digital marketing skills of the residents in Kampung Gerabah Penanggungan through a 10-day training program. Twenty community members participated in the program, where they received training on fundamental aspects of digital marketing, such as social media marketing and search engine optimization (SEO). Additionally, the participants were equipped with knowledge and skills in employing the 4C formula copywriting method, a proven approach for crafting compelling marketing content. The results of the study showed that the training program was effective in improving the participants' knowledge and skills in digital marketing. The participants were able to create effective marketing content for their products and services. They were also able to use social media to reach a wider audience.